2015
DOI: 10.2166/ws.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of water parameters on the flow rate of ceramic pot filters in a long-term experiment

Abstract: Poor water quality is a major contributing factor to disease in developing countries. Silver-coated ceramic pot filters (CPFs) are a relatively common form of household water treatment system (HWTS) representing an effective and sustainable technology for poor communities. Water production seems to be the major limiting factor of the CPF's lifetime and sustainability since low flow rates do not produce an adequate daily volume of treated water. This paper describes a long-term study of CPF flow rates under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…5 as a function of the ambient temperature 53 . In the first hour, the fully filled filters produce an average of 600-950 ml of filtrate 54 .…”
mentioning
confidence: 99%
“…5 as a function of the ambient temperature 53 . In the first hour, the fully filled filters produce an average of 600-950 ml of filtrate 54 .…”
mentioning
confidence: 99%
“…Although ceramic pot filters are considered safe, robust and appropriate technologies, there is also a general consensus that water revenues are limited due to clogging of the ceramic element (Van Halem et al, 2007;Salvinelli and Elmore, 2015;Salvinelli et al, 2017). As part of the quality protocol, filters are tested at the factories for their flow rate, which should be within 1e5 L h À1 limits, depending on the factory (Rayner et al, 2013).…”
mentioning
confidence: 99%
“…A constant head flow rate test of all the filters used in the study was conducted in order to establish a baseline daily average. In order to maintain constant conditions and to maximize the flow rate of each filter over the time in which the experiment was conducted, constant head apparatuses similar to the one described by Salvinelli and Elmore [6] were used, as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…A long-term investigation described by Salvinelli and Elmore [6] showed that flow rates decrease over time and that turbidity negatively affects both the average flow rate and the rate at which it decreases. Mihelcic et al [5] stated that turbidity has a negative impact on many water treatment processes in different ways, including clogging filters and therefore reducing their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation